Development and Standardization of Modified Simultaneous Multifrequency Stimulus for Recording Ocular Vestibular-Evoked Myogenic Potential and Its Interaction with the Alternate Electrode Montages - Raveendran, Rajesh Kumar; Singh, Niraj Kumar (Journal of the American Academy of Audiology, 2024)
Background Simultaneous multifrequency (SiMFy) is a time-saving and reliable stimulus to determine the frequency tuning of ocular vestibular-evoked myogenic potential (oVEMP); however, the absence of 4000 Hz in SiMFy potentially makes it a less potent tool for the diagnosis of superior semicircular canal dehiscence, a pathology with an ever-increasing prevalence. Further, SiMFy was validated using only the infraorbital (IO) electrode montage. However, the recordings obtained using the IO montage might be susceptible to reference contamination introduced by a small separation between the recording electrodes and also susceptible to reflex impurity due to the spatially displaced reference electrode from the inferior oblique muscle, rendering it vulnerable to picking up responses from other muscles. Nonetheless, little is known about the similarities/differences between the SiMFy-induced oVEMPs using alternate montages (belly-tendon [BT], chin-reference [CR], and sternum-reference [SR]) and the nonsimultaneous multifrequency oVEMPs (NSM-oVEMPs) using the IO montage.Purpose of the Study To develop a modified SiMFy stimulus and investigate its effects on frequency tuning of oVEMP using various electrode montages.Research Design Within-subject experimental design.Study Sample Thirty-three healthy adults aged 20 to 30 years.Data Collection and Analysis Tone bursts of octave and mid-octave frequencies from 250 to 4000 Hz were generated and concatenated to create the modified SiMFy stimulus. All participants underwent NSM oVEMPs and modified SiMFy oVEMPs using BT, CR, SR, and IO montages simultaneously. The response rate, peak-to-peak amplitude, and frequency tuning were compared between NSM-oVEMP and modified SiMFy oVEMP and also between the electrode montages.Results BT montage recorded the largest amplitude among the montages in NSM stimulation and modified SiMFy stimulation. Although the response rates were comparable, the modified SiMFy produced significantly lower oVEMP amplitudes than the NSM stimulation within each electrode montage (p < 0.05). A moderate-to-strong agreement on frequency tuning existed between the NSM stimuli and modified SiMFy stimulus for all the montages, except for the SR montage.Conclusions Although the modified SiMFy produces smaller amplitude oVEMPs than the NSM stimulation for the respective montages, its use in combination with the BT montage yields higher response rates and larger peak-to-peak amplitudes than the NSM recording using IO montage.
Keywords: frequency tuning; electrode placements; multifrequency; chained stimuli; VEMP